Graduate entry to medicine: widening psychological diversity - James, David; Ferguson, Eamonn; Powis, David; Bore, Miles; Munro, Don; Symonds, Ian; Yates, Janet (BioMed Central, 2009)
Abstract Background: At Nottingham University more than 95% of entrants to the traditional 5-year medical course are school leavers. Since 2003 we have admitted graduate entrants (GEM) to a shortened (4-year) course to 'widen access to students from more disadvantaged backgrounds'. We have recently shown that the GEM course widens academic and socio-demographic diversity of the medical student population. This study explored whether GEM students also bring psychological diversity and whether this could be beneficial.